Synthesis and Properties of Some 3-Halo Flavones - Bhadange, R.E.; Doshi, A.G.; Raut, A.W. (Asian Journal of Chemistry, 2010)
2-Hydroxy-3-substituted-5-chloro-4´-nitro dibenzoyl methane, 2-hydroxy-3-substituted-5-chloro-4´-amino dibenzoyl methane and 2-hydroxy-3-substituted-5-chloro-4´-chloro dibenzoyl methane react with iodine monochloride in DMF medium or with bromine in DMF medium affording respectively 2-(4´-substituted) 3-halo-6- chloro-8-substituted flavone. The structure of these compounds is confirmed by chemical and spectral data.